2010
DOI: 10.1007/s10562-010-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Supported Vanadium Oxide Catalysts by Pattern Formation

Abstract: The behavior of ultra-thin (\1 ML) films of vanadium oxide on Rh(111) during the H 2 ? O 2 reaction was studied in the 10 -6 -10 -4 mbar range with photoemission electron microscopy (PEEM). One observes that under reaction conditions the V-oxide condenses forming a stripe pattern of macroscopic dimensions on the surface. The pattern is characterized by an intrinsic wave length which obeys a power law dependence on the reactants pressure. The origin of the pattern is discussed within the concept of reactive pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…In an earlier study of the O 2 + H 2 reaction on Rh(111)/VO x it was concluded that chemisorbed oxygen acts as kind of surfactant for VO x reducing the line tension between a VO x island and the surrounding bare metal surface. 17,18 If we assume that chemisorbed oxygen stabilizes the free V n O m clusters on the bare metal surface then in turn a reduced oxygen coverage would have a low concentration of free V-clusters as consequence. This could explain why no nucleation of VO x islands is seen in the bright elliptical area.…”
Section: Coalescence Of Islandsmentioning
confidence: 99%
“…In an earlier study of the O 2 + H 2 reaction on Rh(111)/VO x it was concluded that chemisorbed oxygen acts as kind of surfactant for VO x reducing the line tension between a VO x island and the surrounding bare metal surface. 17,18 If we assume that chemisorbed oxygen stabilizes the free V n O m clusters on the bare metal surface then in turn a reduced oxygen coverage would have a low concentration of free V-clusters as consequence. This could explain why no nucleation of VO x islands is seen in the bright elliptical area.…”
Section: Coalescence Of Islandsmentioning
confidence: 99%
“…It should be pointed out here that due to beam-damaging effects an erroneous coverage calibration was given in a preceding paper, i.e., instead of 0.1 MLE given there, the actual coverage was ∼0.2 MLE. 11 The UHV chamber was operated as a continuous flow reactor, introducing the reactant gases through leak valves. Pressures were measured with an uncalibrated ion gauge; the different ionization probabilities of O 2 and H 2 were taken into account multiplying the p(H 2 ) reading by 2.…”
Section: 8à11mentioning
confidence: 99%
“…Due to its wide applicability, it is important to rationally understand the working principle of the catalyst under different experimental conditions. In this sense, Lovis et al [29,30,46] have used LEEM and PEEM to address the properties of a V x O y /Rh(111) model system, establishing a representative example of what can be done and what kind of information can be extracted from a model system with this approach. For instance, their studies were focused on the dynamic changes that occur on the oxide phase when the model catalyst is exposed to reaction condition, in this case being the hydrogen oxidation reaction.…”
Section: Application In Catalysismentioning
confidence: 99%
“…For instance, their studies were focused on the dynamic changes that occur on the oxide phase when the model catalyst is exposed to reaction condition, in this case being the hydrogen oxidation reaction. Some selected results extracted from reference [46] are shown in Fig. 5.…”
Section: Application In Catalysismentioning
confidence: 99%
See 1 more Smart Citation